Symposium 3: Bridging Cultures in Designing for Learning: An EChina uk Project Case Study - Joyes , Gordon (Proceedings of the International Conference on Networked Learning, 2006)
This paper focuses on collaboration across professional cultures within the Sino–UK collaborative eLearning development projects at the University of Nottingham. It examines how technologists and academics developed a common understanding and effective ways of working. At the beginning of the project, the UK academics were unused to writing for online courses, and were unsure how to go about it. The technologists, on the other hand, simply wanted to be told what they needed to do, and this initially resulted in a communication breakdown. Audio and video recordings of key project meetings together with reflective journal entries and interviews with those involved in the collaboration were used to identify and explore a series of critical incidents that reveal key differences in perspective between the team members. The design approach that the team developed to bridge the differing perspectives is described as well as implications for practice.